Quality of Life Among Medical Students in Nepal: A Comparative Study - Gupta, Anoop Krishna; Sharma, Rakhi; Bashyal, Geeta (Med Phoenix, 2021)
Introduction: Medical education increases mental stress and affects the quality of life in medical students. Tough competition, academic performances, psychological distress, and unhealthy lifestyle add extra burden to the student. The study aimed to compare the quality of life among students of first and final year students. Materials and Methods: This was a cross-sectional study among first and final-year students of Bachelor in Medicine and Bachelor in Surgery (MBBS) degree at National Medical College at Birgunj, Nepal. Pre-designed socio-demographic proforma along with the Kuppuswamy scale was administered to the student. Another scale used was the English version of (World Health Organization Quality of Life-Brief version) WHOQoL-Bref scale. Result: Eighty-one students participated in this study, where 54 students were from the first year and 27 students from an internship. 43.2% of them belonged to the upper socioeconomic class as per the Kuppuswamy scale. The quality of life of interns was higher and better in all domains but was statistically significant in general (0.002), psychological (0.006), environmental (0.002), and overall (0.008) domains. Conclusion: The quality of life of medical students is lower than the general population. It is poorer for the first-year student than the final year interns.